Keperluan Dan Prospek Program Tahfiz Dan Qiraat Di Malaysia: Kajian Kes Di Semenanjung Malaysia - Muhammad Mustaqim Mohd.Zarif; Syed Ahmad Tarmizi Syed Omar; Khairul Anuar Mohamad; Mohd. Fauzi Mohd. Amin; Mohd Alwi Yusoff (Universiti Sains Islam Malaysia, 2024)
Quranic memorization and Qiraat are considered important parts in the fields of Quranic studies. Their importance could be seen in their roles in preserving and ensuring the continuity and authenticity of the Quranic verses from mistakes and errors. As such, many programs are introduced in this field of study at the level of diploma by certified institutions specializing in that field. In the academic planning of 2003, the Faculty of Quranic and Sunnah Studies, Islamic University College of Malaysia, planned to offer a bachelor's degree in the field of Tahfiz and Qiraat studies. Therefore, it is the aim of this research to get the opinions of all the parties related to this program such as the students, teachers in the field of Tahfiz and Qiraat, future employers as well as members of society. Issues such as the necessity and suitability of the program, the capability of students in following the curriculum, and its prospects in academic advancement as well as future employment are the main points to be dealt with in this research. The methodologies adopted in this research include the methods of field research such as the use of questionnaires distributed to and interviews with selected respondents in parts of peninsular Malaysia. The findings indicate that the present level of Tahfiz and Qiraat studies at the diploma level is sufficient to cater to the needs of society. In general, the need for it to be offered at the bachelor's degree level is outweighed by the inadequacy of employment opportunities for its graduates in the job market and thus, must heavily rely on the support and assistance of the government.